First-rate genre reads: the best of the short list - Wyatt, Neal (Library journal (1976), 2010)
Each year the American Library Association's Reference and User Services Association's Reading List Council selects the best genre fiction, providing readers and librarians with an excellent list of suggestions that includes read-alikes for the winning title and a short list of excellent runners-up. ISBN 978-0-312-37703-8. $24.99), the fifth title in Louise Penny's "Three Pines" mystery series, Chief Inspector Armand Gamache of the SÃ»reté du Québec and his team are in the picturesque village to investigate the murder of a hermit. ISBN 978-1-4391-0847-5. pap. $14), Oxford biochemist Steven J. Fisher thinks he's found the cure for female sexual dysfunction, but his latest test subject, "Miss G," a.k.a. Annie Gluck, a Ph.D. candidate who cannot experience orgasm, is wreaking havoc with his research results.